The Effects of Hormone Diets with Different 17β-Estradiol Levels on Growth and Feminization in Long-Whiskered Catfish (Mystus gulio) Larvae Using Conventional and Microencapsulated Feed - Dokkaew, Sahabhop; Songdum, Kritchavat; Prachom, Noratat; Boonyung, Wiwiththanon; Kitikiew, Suwaree; Khamphet, Khwankhao; Waicharoen, Preecha; Na-Nakorn, Uthairat; Paankhao, Natthapong; Uchuwittayakul, Anurak; Kantha, Phunsin (My University, 2026)
Feminization is an important biotechnological approach in aquaculture for species in which females exhibit superior growth and higher market value. The long-whiskered catfish (Mystus gulio), a euryhaline species cultivated in both monoculture and co-culture systems, contributes to sustainable aquaculture by grazing on uneaten feed and maintaining pond cleanliness. This study evaluated the effects of dietary 17β-estradiol (E2) at 0, 10, 30, and 60 mg/kg, incorporated into conventional and microencapsulated feeds, on the feminization and early growth of M. gulio larvae. Treatments were administered during the weaning stage for 14 and 21 days under controlled rearing conditions. Results showed that larvae fed microencapsulated feed containing 60 mg/kg E2 achieved the highest specific growth rate (26.91 ± 1.92%/day), feed efficiency (164.76 ± 33.23%), and feminization success (99.73 ± 0.04%). Hormonal assays confirmed elevated estradiol and reduced testosterone levels, consistent with ovarian development observed in histological sections. Gene expression analysis further supported these findings through the significant upregulation of cyp19a, erb1, and erb2 mRNA levels. Overall, this study demonstrates that microencapsulated hormone feeding is an effective and environmentally responsible strategy for achieving monosex female populations in M. gulio, enhancing productivity, reproductive performance, and sustainability in aquaculture systems.
Keywords: 17β-estradiol; aquaculture sustainability; estrogen-related genes; feminization; growth performance; microencapsulated feed; Mystus gulio; sex reversal